Striatal Cholinergic Interneurons in a Knock-in Mouse Model of L-DOPA-Responsive Dystonia - Yalcin-Cakmakli, Gul; Rose, Samuel J.; Villalba, Rosa M.; Williams, Lagena; Jinnah, Hyder A.; Hess, Ellen J.; Smith, Yoland (Frontiers in Systems Neuroscience, 2018)
Striatal cholinergic dysfunction is a common phenotype associated with various forms of dystonia in which anti-cholinergic drugs have some therapeutic benefits. However, the underlying substrate of striatal cholinergic defects in dystonia remain poorly understood. In this study, we used a recently developed knock-in mouse model of dopamine-responsive dystonia (DRD) with strong symptomatic responses to anti-cholinergic drugs, to assess changes in the prevalence and morphology of striatal cholinergic interneurons (ChIs) in a model of generalized dystonia. Unbiased stereological neuronal counts and Scholl analysis were used to address these issues. To determine the potential effect of aging on the number of ChIs, both young (3 months old) and aged (15 months old) mice were used. For purpose of comparisons with ChIs, the number of GABAergic parvalbumin (PV)-immunoreactive striatal interneurons was also quantified in young mice. Overall, no significant change in the prevalence of ChIs and PV-immunoreactive cells was found throughout various functional regions of the striatum in young DRD mice. Similar results were found for ChIs in aged animals. Subtle changes in the extent and complexity of the dendritic tree of ChIs were found in middle and caudal regions of the striatum in DRD mice. Additional immunohistochemical data also suggested lack of significant change in the expression of striatal cholinergic M1 and M4 muscarinic receptors immunoreactivity in DRD mice. Thus, together with our previous data from a knock-in mouse model of DYT-1 dystonia (Song et al., 2013), our data further suggest that the dysregulation of striatal cholinergic transmission in dystonia is not associated with major neuroplastic changes in the morphology and prevalence of striatal ChIs.